Sándor Márai na Bliskim Wschodzie = Sándor Márai in the Middle East - Zwolińska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article I present a literary record of impressions from a trip made by the twentieth century Hungarian writer Sándor Márai, collected in the volume titled "On a journey". I focus on the sketches in which he describes the experience of a contact between the European other and the exotic East. Márai visited Middle East countries, such as Egypt, Palestine, Lebanon, Syria, as well as Turkey and Greece in 1925.
Keywords: Márai, Sándor (właśc. Grosschmid de Mára, Sándor Károly Henrik; prozaik węgierski; 1900-1989); Bliski Wschód; literatura węgierska; 20 w.